EPAC2: A new and promising protein for glioma pathogenesis and therapy - Seidu A. Richard (Oncology Reviews, 2020)
Gliomas are prime brain cancers which are initiated by malignant modification of neural stem cells, progenitor cells and differentiated glial cells such as astrocyte, oligodendrocyte as well as ependymal cells. Exchange proteins directly activated by cAMP (EPACs) are crucial cyclic adenosine 3’,5’-monophosphate (cAMP)-determined signaling pathways. Cyclic AMP-intermediated signaling events were utilized to transduce protein kinase A (PKA) leading to the detection of EPACs or cAMP-guanine exchange factors (cAMP-GEFs). EPACs have been detected as crucial proteins associated with the pathogenesis of neurological disorders as well as numerous human diseases. EPAC proteins have two isoforms. These isoforms are EPAC1 and EPAC2. EPAC2 also known as Rap guanine nucleotide exchange factor 4 (RAPGEF4) is generally expression in all neurites. Higher EAPC2 levels was detected in the cortex, hippocampus as well as striatum of adult mouse brain. Activation as well as over-secretion of EPAC2 triggers apoptosis in neurons and EPAC-triggered apoptosis was intermediated via the modulation of Bcl-2 interacting member protein (BIM). EPAC2 secretory levels has proven to be more in low-grade clinical glioma than high-grade clinical glioma. This review therefore explores the effects of EPAC2/RAPGEF4 on the pathogenesis of glioma instead of EPAC1 because EPAC2 and not EPAC1 is predominately expressed in the brain. Therefore, EPAC2 is most likely to modulate glioma pathogenesis rather than EPAC1.